Self-determination and leader development. Issue 5 (November 2015) - Solansky, Stephanie T
Self-determination theory serves as the primary explanatory mechanism in this article of significant differences in the outcomes of leader development interventions. A total of 445 organizational administrators in a year-long leadership professional development programme are categorized based on their self-determination. Self-determination is categorized by the initial choice in programme participation and the pursuing choice in programme content and methods. The empirical results show differences based on self-determination categorizations in terms of self-assessments and subordinate assessments. However, the significant differences are not as expected in all cases. Theoretical and empirical contributions are discussed that inform researchers and practitioners.